(untitled) (CIPEEX, 2025)
Pharmacovigilance and haemovigilance are complementary and fundamental areas for ensuring transfusion safety in hemotherapy. This simple abstract addresses the concepts, classification of transfusion reactions, protocols for reporting and investigation, the role of the clinical pharmacist, electronic monitoring systems, epidemiological data in Brazil, current challenges, and the guidelines of ANVISA and the Brazilian Society of Hematology and Hemotherapy (SBHH). The research includes normative analysis, review of technical-scientific literature, assessment of recent national epidemiological data, and examination of monitoring systems and emerging technologies. The regulatory advances of RDC nº 34/2014 and IN nº 196/2022 are highlighted, as are multidisciplinary approaches, the use of the Notivisa system, the evolution of compliance indicators, challenges related to underreporting and professional qualification, and international trends such as AI integration in pharmacovigilance processes. These strategies underpin the continuous improvement of patient safety, process quality, and national institutional effectiveness